Pengaruh Digital Marketing Dan Customer Experience Terhadap Keputusan Orang Tua Memilih Sekolah XYZ - Antonius Andhika Wahyudi; Siti Nurjanah (Research and Community Service UNIVERSITAS KALBIS, 2025)
Intense competition among schools during the enrollment period for new students is experienced by XYZ School, specifically SMP Katolik within the XYZ Association located in Koja, North Jakarta. This competition is evidenced by the trend of new student registrations towards the end of the enrollment period. It compels XYZ School to increase the number of new student admissions through the influence of Digital marketing and Customer experience, aiming to stimulate parents' interest in decision-making. The objective of this research is to analyze the impact of Digital marketing and Customer experience on influencing parents' interest in decision-making. The study population comprises 318 student’s parents. This research is quantitative, employing inferential statistical analysis and descriptive statistics. The results indicate that Digital marketing does not have a significant influence on parents' interest in registering their children at SMP XYZ, with direct and indirect impact values of 0.06 and 0.03, respectively. Conversely, Customer experience significantly influences parents' interest in deciding to enroll their children at SMP XYZ, with direct and indirect impacts of 0.33 and 0.57, respectively. Therefore, the school can establish a dedicated digital marketing division with research and development teams on creating compelling enrollment content.